WASHINGTON VIEW: Why education doesn't work — an introduction. (October 2014) - Ferguson, Maria
The author intended to write a column about how things work in education, using a popular book as a guide. But the more thought that went into it, its seemed the best way to describe the education world is in why things don't work. Briefly, education has four major sector levels: federal, state, local, and school. And they interact dysfunctionally with each other and in and among other civic and philanthropic groups and stakeholders.